Comparison of Leaf and Fine Root Traits Between Annuals and Perennials, Implicating the Mechanism of Species Changes in Desertified Grasslands - Ning, Zhiying; Li, Yulin; Zhao, Xueyong; Han, Dan; Zhan, Jin (Frontiers in Plant Science, 2022)
Annual species show traits such as short leaf lifetimes, higher SLA and leaf nutrient concentrations that provided a more rapid resource acquisition comparing to perennials. However, the comparison of root traits between the annuals and perennials is extremely limited, as well as the trade-offs of leaf and fine root traits, and resource allocation between leaf and root, which may provide insight into the mechanism of species changes in arid and semi-arid areas. With lab analysis and field observation, 12 traits of leaf and fine root of 54 dominant species from Horqin Sandy Land, Northeastern China were measured. The organization of leaf and fine root traits, and coordination between leaf and fine root traits of annual and perennial plants were examined. Results showed that there were differences between annuals and perennials in several leaf and fine root traits important in resource acquisition and conservation. Annuals had higher leaf area (LA), specific leaf area (SLA), and specific root length (SRL) but lower leaf dry-matter content (LDMC), leaf tissue density (LTD), leaf carbon concentration (LC), and fine root dry-matter content (FRDMC) than perennials. Leaf nitrogen concentration (LN) and fine root nitrogen concentration (FRN) were negatively related to LTD and FRDMC in annuals, while FRN was positively related to FRTD and fine root carbon concentration (FRC), and LA was positively related to LN in perennials. These implied that annuals exhibited tough tissue and low palatability, but perennials tend to have smaller-leaves to reduce metabolism when N is insufficient. Annuals showed significant positive correlations between FRC/FRDMC and LDMC/LTD/LC, suggesting a proportional allocation of photosynthate between leaf and fine root. In perennials, significant negative correlations were detected between LN, LC and SRL, fine root tissue density (FRTD), as well as between LA and FRTD/FRC. These indicated that perennials tend to allocate more photosynthate to construct a deeper and rigid roots system to improve resource absorption capacity in resource-limited habitat. Our findings suggested that annuals and perennials differed considerably in terms of adaptation, resource acquisition and allocation strategies, which might be partly responsible for species changes in desertified grasslands.